P187 Workforce planning and SAS Doctors: a crisis in waiting - J Lee; E Carlin; A Robinson (Sexually Transmitted Infections, 2012)
Background The importance of medical workforce planning is well recognised but it is an inexact science and has usually concentrated on consultant and trainee numbers. The difficulties in planning are complicated by a lack of information on specialty and associate specialist (SAS) doctors. Aims We sought to aid workforce planning by collecting data from the SAS workforce to enable broader sexual health service planning. Methods A survey monkey questionnaire was devised and sent to all SAS doctors in sexual health who were known to the British Association for Sexual Health and HIV (BASHH) or its members. The survey was open for completion for 3 months from March 2011. Results In total, 227 SAS doctors (78% female, 22% male) completed the survey, 74% were on the new SAS contract, 44% as specialty doctors, 30% as associate specialists. Uptake was estimated at 40% on local assessment. According to the data in abstract P187 table 1, 1049–1253 genitourinary medicine (GUM) sessions/week are done by the respondents. Numbers are likely to be much higher given the estimated response rate. Significant numbers of HIV and sexual and reproductive health (SRH) sessions are also undertaken. Respondents indicated that 63% planned to retire within the next 15 years; 11% by 2013, 18% between 2014 and 2016, 20% between 2017 and 2022, 21% between 2022 and 2026, 29% were unsure when in the next 15 years they would retire. Abstract P187 Table 1 Number of sessions performed by SAS doctors % of SAS doctors working these sessions Number of GUM sessions/week 1–2 20 3–4 20 5–6 17 7–8 15 9–10 18 ≥10 3 Number of HIV sessions/week None 74 1–2 19 3–4 2 5–6 2 7–8 2 9–10 0.5 Number of SRH sessions/week None 49 1–2 24 3–4 10 5–6 7 7–8 4 9–10 5 Conclusion SAS doctors provide a major contribution to sexual health service work and given that 63% plan to retire within the next 15 years this is a crisis in waiting. Failure to take this data into account when planning for the future may mean that the crisis will become a reality.